Трансформації зайнятості як фактор зміни мотиваційних моделей поведінки на ринку праці - Семикіна, М. В.; Іщенко, Н. А.; Бугайова, М. В.; Semykina, M.; Ischenko, N.; Bugaeva, M. (КНТУ, 2015)
У статті розкрито сутність трансформацій зайнятості в країнах ринкової економіки і в Україні. Проаналізовано сучасні тенденції трансформацій зайнятості на ринку праці України. Визначено вплив трансформацій занятості на зміну мотиваційних моделей поведінки на ринку праці. Розкрито аспекти мотивації пошуку роботи в залежності від вікових груп. Визначено та обґрунтовано типові мотиваційні моделі поведінки з урахуванням інноваційних змін на ринку праці. The purpose of the article is to reveal the essence and features of employment transformations in Ukraine, define the obstacles in realization of competitive advantages of youth in the conditions of dynamic changes on the Ukrainian labor market, opportunities of their overcome. In the course of research the general scientific and special methods of research (the comparative, economical and statistical, sociological analysis) have been used. It is proved that transformation of employment results from cardinal changes of demand for work as a result of globalization, informatization, competition, predetermining distribution of nonconventional forms of employment etc.
Transformation of Employment as a Factor of Changing in Motivating Models of Behavior in the Labor Market
Keywords: трансформація зайнятості; нестандартна зайнятість; безробіття; мотиваційні моделі поведінки; employment transformation; competitive advantages; non-standard employment; unemployment; youth employment